Estimating building cooling energy demand through the Cooling Degree Hours in a changing climate: A modeling study. (January 2022) - Salata, Ferdinando; Falasca, Serena; Ciancio, Virgilio; Curci, Gabriele; Grignaffini, Stefano; de Wilde, Pieter
Highlights: Cooling degree hours are used to estimate cooling energy need;. Local conditions will weigh more than latitude on future building cooling energy consumption;. Ambient temperatures are simulated to map the growth of cooling energy needs in Italy;. Buildings in densely populated areas will need higher cooling capacity over longer periods;. Energy needs in 2050 under RCP8.5 scenario and in 2080 under RCP4.5 will be similar. Abstract: The increasingly hot and long summers due to the climate change will cause a significant increase in energy demand for cooling systems, especially in highly-densely populated regions. The cooling energy needs of buildings are proportional to the Cooling Degree Hours, which consist in the cumulative sum of the positive differences between the hourly outdoor temperature and the indoor comfort temperature. In this work, this quantity is computed using gridded temperatures predicted by the Weather Research and Forecasting model for the years 2000, 2019, 2050 and 2080 across Italy. This allows investigating the evolution of the cooling energy needs on a national scale, following the climate-change related trend of the ambient temperature. For climate projections, an intermediate (RCP4.5) and a high emissions (RCP8.5) scenario defined by the Intergovernmental Panel for Climate Change have been considered. Findings show that results of 2050-RCP8.5 and 2080-RCP4.5 are very close, both in terms of amount of operational hours and cooling degree hours. The maximum level of cooling degree hours has increased more in the recent past than it will grow in the future, even according to RCP8.5. Yet in 2080 about 70% of Italy will reach levels of cooling degree hours not touched in 2000.